RUMINAL BUTYRATE INFUSION INCREASED PAPILLAE SIZE AND DIGESTA WEIGHT BUT DID NOT CHANGE LIQUID FLOW RATE IN THE RUMEN OF GOATS - M. Moolchand; J. Wang; H. Gui; Z. Shen (Journal of Animal and Plant Sciences, 2013)
This study investigated the effects of ruminal infusion of butyrate on digesta weight and liquid flow in rumen. Goats (n=15) fed concentrates 200 g/day and hay ad libitum, were assigned into two groups: control (C, n=7) and butyrate (B, n=8) and were intraruminally infused with 0.3 (B group) or 0 (C group) g/kg.BW/day sodium butyrate, dissolved in potassium buffer (50 ml), before morning feeding for 4 weeks. Liquid flow in the rumen was determined by pulse dosing of cobalt-ethylene diamine tetra acetic acid (Co-EDTA) into the rumen. The papillae height and the thickness of epithelium increased (P < 0.05) in B compared to C. The full weight of rumen and the weight of rumen digesta, expressed as percent of total stomach weight, were greater in B than in C (P = 0.04 and 0.06, respectively), but the full weight of omasum and the weight of omasal digesta were lower in B than in C (P = 0.05 and 0.07, respectively). Ruminal volume, liquid turn over and liquid outflow rate did not differ (P > 0.05) between groups. It was concluded that ruminal infusion of butyrate increased papillae size and digesta weight but did not change liquid passage rate in the rumen of goats.
Keywords: rumen papillae; rumen digesta; liquid passage rate; goat